THE INFLUENCE OF ISLAMIC LEADERSHIP ON MOTIVATION AND PERFORMANCE OF EMPLOYEES IN ISLAMIC BANKS IN EAST KALIMANTAN PROVINCE - Wati, Maria (STIT Ibnu Rusyd Tanah Grogot, 2025)
The purpose of this study is to prove and analyze the influence of Islamic leadership on hafizun at Islamic banks in East Kalimantan Province and to prove and analyze the influence of Islamic leadership on al-Kasbu at Islamic banks in East Kalimantan Province. This study employs a quantitative and qualitative approach, which is useful for describing the existence and role of a research object or variable in relation to other research variables in a descriptive manner, by conducting a statistical analysis of the causal relationship between the research variables. The results of this study are that Ri'asatul Islam has a significant positive influence on Hafizun, meaning that the better the application of Islamic values in Islamic leadership at Islamic banks in East Kalimantan Province, with indicators of honesty, responsibility, professionalism, wisdom, fairness, monotheism, gentleness, and noble character, the higher the Hafizun with indicators of beneficial, fortunate, seeking wealth through worship, working with the heart, seeking Allah's pleasure, inner peace, living for the Hereafter, and being righteous. This is proven by the increasing values of all Islamic leadership indicators, where the graphical trend has been increasing over the past five years, starting from 2008 to 2012. Ri'asatul Islam has a significant positive influence on al-Kasbu, where the better the application of Islamic values in Islamic leadership at Islamic Banks in East Kalimantan Province, the higher the al-kasbu of employees will be, thereby improving the spiritual performance of employees with the following indicators: performance, speed/accuracy, service, quality of work, increased Zakat, Infaq, and Shadaqah (ZIS) contributions, increased sunnah worship, discipline, and efficiency. This is evidenced by the increasing values of all Islamic leadership indicators, with a rising trend over the past five years, from 2008 to 2012.